Modulation of VEGF signaling in a mouse model of diabetes by xanthohumol and 8‐prenylnaringenin: Unveiling the angiogenic paradox and metabolism interplay. Issue 4 (30th January 2017) - Costa, Raquel; Rodrigues, Ilda; Guardão, Luísa; Lima, Joana Quelhas; Sousa, Emília; Soares, Raquel; Negrão, Rita
Abstract : In type 2 diabetes mellitus there is an angiogenic paradox with increased vascularization VEGF‐A levels and VEGFR‐2 signaling activation in tissues as kidney, together with a reduction in the same pathway in the left ventricle. Consumption of polyphenols, xanthohumol, and 8‐prenylnaringenin, reverses the angiogenic paradox in a tissue‐dependent manner, rendering them interesting agents to control diabetic‐related vascular complications. Abstract : Scope: Imbalance in kidney and heart neovascularization is common in type2 diabetes (T2DM) patients. Nevertheless, the mechanisms governing this angiogenic paradox have not been elucidated. Xanthohumol (XN) and 8‐prenylnaringenin (8PN) beer polyphenols modulate angiogenesis, being thus targets for T2DM‐related complications. Our work examined whether polyphenols consumption affects angiogenic paradox and metabolism in a T2DM mouse model. Methods and results: An increase in kidney and a reduction in left ventricle (LV) microvessels of diabetic C57Bl/6 mice were observed. XN consumption reduced angiogenesis, VEGFR‐2 expression/activity, VEGF‐A and phosphofructokinase‐2/fructose‐2, 6‐bisphosphatase‐3 enzyme expression, a metabolic marker present in endothelial tip cells in T2DM mice kidney. 8PN had opposite effects in T2DM mice LV. These XN and 8PN effects were dependent on VEGF levels as revealed by in vitro assays. These findings were accompanied by tissue and plasma reduced expression levels of VEGF‐B and its receptors, VEGFR1 and neuropilin‐1, by both polyphenols. Conclusion: Beer polyphenols modulate T2DM angiogenic paradox in a tissue‐dependent manner. We also show for the first time that both polyphenols decreased VEGF‐B pathway, which is implicated in endothelial‐to‐tissue lipid metabolism. Altogether, the effects of these polyphenols in the crosstalk between angiogenesis and metabolism render them potent agents for novel diabetic therapeutic interventions.